Numerical Simulation of Breast Cancer in the Early Diagnosis with Actual Dimension and Characteristics Using Photoacoustic Tomography - Maryam Ahangar Darband; Esmaeil Najafi Aghdam; Arash Gharibi (Archives of Acoustics)
A numerical study and simulation of breast imaging in the early detection of tumors using the photoacoustic (PA) phenomenon are presented. There have been various reports on the simulation of the PA phenomenon in the breast, which are not in the real dimensions of the tissue. Furthermore, the different layers of the breast have not been considered. Therefore, it has not been possible to rely on the values and characteristics of the resulting data and to compare it with the actual state. Here, the real dimensions of the breast at threedimensional and different constituent layers have been considered. After reviewing simulation methods and software for different stages of the PA phenomenon, a single suitable platform, which is commercially available finite element software (COMSOL), has been selected for simulating. The optical, thermal, elastic, and acoustic characteristics of different layers of breast and tumor at radiated laser wavelength (800 nm) were accurately calculated or obtained from a reliable source. Finally, by defining an array of 32 ultrasonic sensors on the breast cup at the defined arcs of the 2D slices, the PA waves can be collected and transmitted to MATLAB software to reconstruct the images. We can study the resulting PA wave and its changes in more detail using our scenarios.